2000
DOI: 10.1080/13606710050084847
|View full text |Cite
|
Sign up to set email alerts
|

A critical evaluation of training needs for child protection in UK sport

Abstract: SummaryChild protection is a relatively new topic in sport about which there was no professional education until the mid-1990s. This paper presents the findings from a study of delegates attending twelve, regional, one-day National Coaching Foundation courses for policy makers in sport during 1997 and 1998 (n= 235). The course was designed to give delegates a basic awareness of the different forms of child abuse and protection and was intended to help them develop appropriate policies and procedures for child … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 6 publications
1
16
0
1
Order By: Relevance
“…(This does not add up to 100 per cent as some institutions use more than one method of delivery.) These results suggest that there is an absence of knowledge within core staff, supporting the conclusions of Carpenter (2005) and Malkin et al (2000) that CP within the education system is lacking.…”
Section: Course Content and Teaching Methodssupporting
confidence: 77%
“…(This does not add up to 100 per cent as some institutions use more than one method of delivery.) These results suggest that there is an absence of knowledge within core staff, supporting the conclusions of Carpenter (2005) and Malkin et al (2000) that CP within the education system is lacking.…”
Section: Course Content and Teaching Methodssupporting
confidence: 77%
“…Even within sport research, variation in interpretation of the concepts of sexual harassment and abuse is evident across different studies (e.g., Cense, 1997;Crosset, 1986;Hassall, 2000;Malkin, Johnston, & Brackenridge, 2000;Toftegaard, 1998;Volkwein et al, 1997) and different countries as shown above (e.g., Australia, Canada, United Kingdom, the Netherlands, and Denmark). For the purposes of the project presented in this paper, the definitions adopted are those as set out in Brackenridge (1997; see Figure 1).…”
Section: Roes: March 2003mentioning
confidence: 93%
“…They have argued that these programmes lead to the premature de-selection of many talented young athletes due to the static nature of testing criteria and the bias towards early maturers (Abbott et al 2005). As Green (2007) also highlights it remains to be seen whether the focus on early talent identification in sport can be reconciled with the growing focus on children's rights, particularly the shift from a 'needs-based' to 'rights-based' approach to youth sport (see also Malkin et al 2000).…”
Section: Are Sport Policy Problems Wicked?mentioning
confidence: 95%